1999
DOI: 10.1046/j.1523-1755.1999.00786.x
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography overestimates left ventricular mass in hemodialysis patients relative to magnetic resonance imaging

Abstract: Echocardiography significantly overestimates LV mass relative to MRI in the presence of LVH and dilation. This overestimation is the result of assumptions made in the calculation of mass from echocardiography M-mode images, which are invalid when LV geometry is abnormal. This error is therefore amplified in dialysis patients, the majority of whom have LVH and in whom intravascular volume is constantly changing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
103
1
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(114 citation statements)
references
References 17 publications
(1 reference statement)
6
103
1
4
Order By: Relevance
“…They identified factors that increase cardiac preload (e.g., salt and water retention, presence of arteriovenous fistulas and anemia), afterload (hypertension, calcific arteriosclerosis), and humoral factors (in- cluding PTH and catecholamines) (20,21); however, there are conflicting results, presumably as a result, in part, of the unreliability of echocardiographic measurement of LVMI in HD patients (12). This is the first study to identify independent determinants of LVMI and LVH in HD patients using CMR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They identified factors that increase cardiac preload (e.g., salt and water retention, presence of arteriovenous fistulas and anemia), afterload (hypertension, calcific arteriosclerosis), and humoral factors (in- cluding PTH and catecholamines) (20,21); however, there are conflicting results, presumably as a result, in part, of the unreliability of echocardiographic measurement of LVMI in HD patients (12). This is the first study to identify independent determinants of LVMI and LVH in HD patients using CMR.…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been established as the most accurate noninvasive method of assessing ventricular dimensions in patients, including those with stage 5 chronic kidney disease (10,11). In particular, measurements obtained by echocardiography tend to overestimate LVMI, particularly at higher values, when compared with CMR (12). Furthermore, pilot studies in patients with ESRD, using CMR to identify myocardial changes of uremic cardiomyopathy, have so far shown a significant reduction in long-term survival similar to previous echocardiography findings (13 and unpublished data).…”
mentioning
confidence: 99%
“…The LIFE investigators also suggested that by using both criteria for the diagnosis of LVH they were able to select a study population enriched by a broader spectrum of risk factors. It has also been reported that echocardiography overestimated the left ventricular mass in patients on haemodialysis, presumably because of its dependence on ventricular volume, suggesting that prior studies using echocardiographic techniques may have overestimated the incidence of LVH [31]. Indeed, in a recent study it was shown that electrocardiographic diagnosis of LVH might be superior to echocardiography in diagnosing patients at high risk for ischaemic strokes [32].…”
Section: Discussionmentioning
confidence: 99%
“…14 Furthermore, M-mode echocardiography consistently overestimates the LVM in the presence of LVH. [15][16][17] Finally, the accuracy and the reproducibility of LVM, as measured by M-mode echocardiography, have been shown to be poor compared with direct measurement by 3D cardiac MRI. 18 This implies that the ECG criteria have been validated against a variable reference standard.…”
mentioning
confidence: 99%